2020
DOI: 10.1515/ijamh-2020-0087
|View full text |Cite
|
Sign up to set email alerts
|

An initiative to limit screen-time in children aged between 6 and 18 years in an urban area in Puducherry: a qualitative study

Abstract: BackgroundRecently television viewing and use of computers have increased considerably and has become a necessary evil in the society. The amount of Screen Time (ST) exposure of a child largely depends on the views of their parents. Screen time among adolescents have resulted in multiple problemsObjectiveTo explore the perceptions of parents of children aged 6–10 years and adolescents of 11–18 years residing in an area of urban Puducherry regarding screen-time and develop health education material to decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The United States has the highest number of studies with n=7 [18], [20], [33], [38], [40], [42], [43]. India follows this with n=5 studies [15], [17], [29], [36], [41]. There are n=3 studies found in Pakistan [24], [26], [28] suggesting a growing awareness of the importance of understanding children's screen time in the country.…”
Section: Distribution Of Past Studiesmentioning
confidence: 96%
See 4 more Smart Citations
“…The United States has the highest number of studies with n=7 [18], [20], [33], [38], [40], [42], [43]. India follows this with n=5 studies [15], [17], [29], [36], [41]. There are n=3 studies found in Pakistan [24], [26], [28] suggesting a growing awareness of the importance of understanding children's screen time in the country.…”
Section: Distribution Of Past Studiesmentioning
confidence: 96%
“…In 2019, the number of studies on children's screen time was relatively limited, with n=3 [12]- [14]. The number of studies increased in 2020 with n=4 [15]- [18], indicating growing concern about the effects of screen time on children's health and development. In 2021, the number of studies significantly increased to n=9 [19]- [27].…”
Section: Distribution Of Past Studiesmentioning
confidence: 99%
See 3 more Smart Citations